A techno-economic evaluation of Virtual Net Metering for the Australian community housing sector. (1st March 2020) - Shaw-Williams, Damian; Susilawati, Connie
Highlights: A novel evaluation of Virtual Net Metering for Community housing is conducted. Virtual Net Metering provides cost effective aggregations for energy pooling. By pooling resources savings up to 18% could be offered for solar only schemes. Battery prices need to decline by 30% for solar and batteries to achieve parity. Abstract: In a climate of soaring energy prices in Australia not all consumers are able to afford the upfront investment costs in photovoltaics to manage their energy costs. Virtual Net Metering enables the sharing of generation and storage benefits against the load of decentralised customers including apartments. The aggregation of resources can reduce the cost for monitoring and managing distributed generation. This is possible by the use of innovative technology for monitoring, billing and settlement software. This paper provides a novel evaluation of virtual net metering to address social equity in the energy transition with regard to the Australian community housing sector. Modelling was conducted with Monte Carlo simulations of weather variables, demand and solar generation. Scenarios of solar only and solar combined with batteries are evaluated. Results showed that by pooling resources savings up to 18% of total energy costs could be offered to participants for solar only schemes whereas battery prices would have to decline by 30% for combined solar and battery schemes to achieve the same.